Multiple distant metastases arising from a single, low-grade rectal neuroendocrine tumor: an autopsy case report - Keng Wee Goh; Hiroshi Yoshida; Ichiro Miura; Chisako Miura; Kazuaki Norita; Takayuki Ii; Hideaki Yamanami; Koju Kobayashi (Journal of Medical Case Reports, 2023)
Abstract Background Rectal neuroendocrine neoplasms are rare epithelial neoplasms of the rectum. The incidence of these tumors has increased over the past decades. However, many questions remain unanswered regarding their clinicopathology, including the possible mechanisms in which these tumors may grow and metastasize. Case presentation In this case report, we report the findings of an autopsy of a 65-year-old Japanese woman diagnosed with multiple liver metastases from a single, low-grade rectal neuroendocrine tumor. The diagnosis was made in late 2018 to early 2019, and subsequently the patient underwent several rounds of standard chemotherapy. However, due to unfavorable side effects, she opted for palliative care at our hospital instead from December 2020. The patient’s condition was generally stable for the next 17 months, but in May 2022, she was hospitalized for increased abdominal pain. Despite enhanced pain control therapy, she eventually passed away. An autopsy was conducted to determine the exact cause of death. The primary rectal tumor was found to be small, but showed strong histological evidence of venous invasion. Metastases in the liver, pancreas, thyroid gland, adrenal glands, and vertebrae were also present. On the basis of the histological evidence obtained, we deduced that the tumor cells may have mutated and gained multiclonality as they spread vascularly to the liver, contributing to the distant metastases. Conclusions The results from this autopsy may provide an explanation for the possible mechanism by which small, low-grade rectal neuroendocrine tumors metastasize.